A study of gametocidal and resistance genes which were transferred to wheat through interspecific hybridisation - Middleton, Felix Lyon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1998.